The nexus between zakat and poverty reduction, is the effective utilization of zakat necessary for achieving SDGs: A multidimensional poverty index approach. Issue 3 (8th October 2020) - Aziz, Yasir; Mansor, Fadillah; Waqar, Shujaa; Haji Abdullah, Luqman
Abstract: This study develops and validates a comprehensive mechanism for evaluating the effect of zakat (obligatory alms‐giving) on reducing poverty and attaining some of the prominent Sustainable Development Goals. The study unconventionally analyzes the effect of macrolevel data on microlevel data on district level of Khyber Pakhtunkhwa, Pakistan. Microlevel data are utilized from a renowned national survey, Pakistan Social and Living Standards Measurement Survey (PSLM) from which the Multidimensional Poverty Index (MPI) has been computed, whereas the macrolevel data have been collected from Zakat & Usher Department Khyber Pakhtunkhwa. Based on the nature of nested data set, we have used a multilevel model to counter intra‐class correlation. The findings confirmed and validated that the novel aspect of the zakat negatively affects the multidimensional poverty and portray significant contribution in targeting several Sustainable Development Goals (SDGs) in Pakistan. Based on the empirical evidence, Zakat being as an obligatory arm which equips individuals to fulfill their necessities, this paper suggests necessary strategies toward zakat disbursement. The mechanism should be refined to stimulate economic growth and pursue SDGs via financial empowerment of less advantaged class of society by reducing poverty in developing countries like Pakistan. Moreover, the methodology adopted in the study opens doors for more enabling and conducive research practices in order to decompose the results and design policies accordingly.